2021
DOI: 10.1126/scitranslmed.abd7789
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal delivery of antibodies has therapeutic effects in animal models of botulism

Abstract: Botulism is caused by a potent neurotoxin that blocks neuromuscular transmission, resulting in death by asphyxiation. Currently, the therapeutic options are limited and there is no antidote. Here, we harness the structural and trafficking properties of an atoxic derivative of botulinum neurotoxin (BoNT) to transport a function-blocking single-domain antibody into the neuronal cytosol where it can inhibit BoNT serotype A (BoNT/A1) molecular toxicity. Post-symptomatic treatment relieved toxic signs of botulism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…To date, only a few publications have shown beneficial treatment of botulism with experimental INABDs [21,[27][28][29][30][31][32][33][34]. Due to the absence of approved INABDs, the proof of concept of our model, in terms of measuring the beneficial effects of potential anti-BoNT/A compounds, was assessed by pharmaceutical antitoxin.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few publications have shown beneficial treatment of botulism with experimental INABDs [21,[27][28][29][30][31][32][33][34]. Due to the absence of approved INABDs, the proof of concept of our model, in terms of measuring the beneficial effects of potential anti-BoNT/A compounds, was assessed by pharmaceutical antitoxin.…”
Section: Discussionmentioning
confidence: 99%
“…All BoNTs have a catalytic light chain (LC), which is a Zn 2+ -endopeptidase that specifically cleaves neuronal SNARE proteins and is mainly responsible for BoNT’s neurotoxic effects, while the heavy chain (HC) mediates toxin attachment to neurons and delivers the LC into the cytosol. Two recent reports demonstrated that animals with symptomatic botulism can be rescued by treatments with biomolecular antidotes consisting of an atoxic BoNT delivery vehicle fused to VHHs that bind and inhibit the LC of the intoxicating BoNT [ 9 , 10 ]. These findings suggest that more effective botulism antidotes will be possible with the identification of VHHs possessing higher potency to inhibit the LC of BoNT, particularly those that are broadly active on most or all natural subtypes of each BoNT serotype.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that, after this toxin consumed and absorbed in the intestines would be visible muscle paralysis in the respiratory and cardiac system, suffocation, heart failure, and death, the mortality rate is between 30% and 60% [33][34][35][36]. It has been shown that botulism is caused by a potent neurotoxin that blocks neuromuscular transmission, resulting in suffocation [37]. Gastrointestinal symptoms are common in food botulism (nausea, vomiting, abdominal pain, diarrhea, dry mouth) and may precede neurological syndromes [38].…”
Section: Resultsmentioning
confidence: 99%